Using Pictures for Teaching Vocabulary to the Junior High School Students - Khafidhoh Khafidhoh; Anita Carolina (Universitas Ahmad Dahlan, 2019)
The research objective is to investigate the impact of using pictures for teaching vocabulary. The research belongs to experimental study. The study population was seventh-grade students of SMP N 2 Imogiri. While two groups or classes of the population as the sample, they are experimental and control group. The data collection technique used was pre-test and post-test. The research findings were the impacts of using pictures, and the pre-test and post-test mean score. First, the impacts of using pictures can improve the students' score, besides it also can draw the students' attention, and students enjoyed and want to participate in the instructional process. Second, the pre-test mean score of the experimental group was 63.04 and the control group was 70. While the post-test mean score of both groups had increased, the mean score of the experimental group was 90.54, and the control group was 84.29. The result of t-test indicated that there is a significant difference in students' vocabulary achievement between both groups. Then, the Sig. (2-tailed) was 0.009 which is lower than 0.05 (0.009<0.05). Thus, the Ha of the hypothesis was accepted. It can be concluded that there is a significant difference in students’ vocabulary achievement of students between both groups.